PENGARUH UNSUR CUACA TERHADAP PERSEBARAN KASUS DEMAM BERDARAH DENGUE (DBD) DI KOTA PADANG TAHUN 2020 - Robet Triarjunet; Ahyuni Ahyuni (JURNAL BUANA, 2022)
ABSTRACT The purpose of this study is to find out the spread of dengue incidence cases in Padang City in 2020, knowing the correlation and influence of weather elements (rainfall, temperature, and wind speed) with the incidence of Dengue Hemorrhagic Fever (DHF) in Padang City in 2020 with variables used, namely cases of DBD by name by address, rainfall, temperature, and wind speed. The method used is nearest neighbor analysis to determine the pattern of distribution of DBD cases, bivariate statistics by using linear correlations and multivariate statistics by using geographically weighted regression (GWR) modeling. The results of the study showed the number of cases of DBD Kota Padang in 2020 as many 292 cases, the pattern of distribution of dengue cases from January to December has a pattern of distribution that clustered with the value range T = 0.36 - 0.63. The results of the analysis of Pearson Product Moment correlation of DBD events with weather elements namely rainfall (r = 0.261) (pvalue = 0.413), temperature (r = 0.580) (p value = 0.048) and angina speed (r = -0.635) (p value = 0.027), the results of geographically weighted regression modeling analysis i.e. rainfall (R2 0.22 - R2 0.25), 22 villages, (R2 0.26 –R2 0.49), 82 villages, temperature (R2 0.14 – R2 0.25), 30 villages, (R2 0.26 – R2 0.50) 34 villages, (R2 0.51 – R2 0.75) 30 villages, (R2 0.76 – R2 0.85) 8 villages, and wind speeds (R2 0.018 – R2 0.24) 104 villages. Keywords: Relationships, Influences, Bivariates, and Multivariates